Architecture of the regional satellite augmentation system for maritime applications - Dimov Stojce Ilcev (Universitas Ahmad Dahlan, 2020)
This paper describes architecture of regional satellite augmentation system (RSAS) in the function of the maritime space communications, navigation and surveillance (CNS) and global navigation satellite systems (GNSS) networks for enhanced safety and surveying of oceangoing ships, management and tracking of cargo, security of Mariners onboard commercial and passenger ships, yachts, sea platforms and other types of craft. The RSAS network are designed to improve vessel management and transport operation because of the enormous expansion of the world's merchant fleet. However, this network with a special ship tracking system can also improve the protection of merchant ships and their crews against piracy, violence, robbery and terrorist attacks. The international maritime organization (IMO) and shipping flag states have project for development of the international ship and port security (ISPS) and design to implement an approaching and port control system (APCS) by special code for all merchant vessels including determination, tracking and positioning of all ships movements in and out of the seaport area. The Maritime RSAS and CNS systems are integration components of the global satellite augmentation systems (GSAS) of two operational GNSS-1 military networks, such as the US global position system (GPS) and Russian global satellite navigation system (GLONASS). In this paper are also introduced the special effects of the ships RSAS networks and coastal movement guidance and control (CMGC) system for maritime application at sea and in seaports areas.